Risky sexual behavior and sexually transmitted infections among men who have sex with men and purchase sex attending an Israeli sexually transmitted infection clinic. (March 2020) - Rich, Rivka S; Leventhal, Alex; Sheffer, Rivka; Mor, Zohar
Men who have sex with men (MSM) and purchase sex (MPS) are a sub-group potentially at high risk for acquiring and transmitting sexually transmitted infections (STIs). This is a hard-to-reach population resulting in a scarcity of studies covering the issue. This cross-sectional study aimed to assess the association between purchasing sex and high-risk behaviors related to HIV/STI transmission and appraise the STI prevalence among MSM. All MSM who attended the STI clinic in Tel Aviv between 2003 and 2010 were included. Demographics, behavioral, clinical, and laboratory data were compared between MPS and non-MPS to identify high-risk sexual behaviors and STI prevalence associated with purchasing sex. Of the first visits of 2694 MSM who attended the STI clinic during the study period, 151 (5.6%) paid for sex. MPS were more commonly older and married than non-MPS. MPS were more likely to engage in behaviors associated with high risk for HIV/STI transmission, including infrequent condom use during anal sex, substance use during sex, and selling sex themselves. MPS had a higher STI prevalence than non-MPS, although this was not statistically significant ( p  = 0.05). These findings highlight the need to establish culturally tailored interventions for MPS addressing the potential risks associated with purchasing sex.